THE STUDY OF THE INDONESIAN PRAGMATIC PARTICLE SIH - Rofiq, Zainur (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2018)
Indonesian is a relatively particle-rich language used mostly in casual speech. However, the study on the pragmatic functions of the language is very few and indebted much solely to the works of Ikranagara (1975), Sari (2008), and of Wouk (1998 2001). The present study aims to need to extend other functions of the particle sih in particular providing wider range of pragmatic functions than the previous work did. The data of the stuy derived from YouTube videos of live Indonesian unscripted talk show; and thus the conversations occur naturally during the program. The results reveal that marking an interrogative statement with sih following WH-words implies that the speaker emphasizes his main inquiry (e.g. ‘where’ emphasizes location) and urges the recipient to answer appropriately. Further, the study extends Sari (2008) and Wouk’s (2006) findings that sih is not only used to emphasize the topic or main point of WH-interrogative statement, but also it applies to declarative statement.